2015
DOI: 10.26530/oapen_579612
|View full text |Cite
|
Sign up to set email alerts
|

A Philosophical Examination of Social Justice and Child Poverty

Abstract: List of Tables vi Acknowledgments vii Introduction: Philosophy and Child Poverty 1 Social Justice for Children-A Capability Approach 1.1 The currency of justice 1.2 Selecting functionings and capabilities for children 1.3 Sufficiency and equality 1.4 Conclusions 2 The Injustice of Child Poverty 2.1 Concepts and measures of child poverty 2.2 The Ill-Being and Ill-Becoming of child poverty: physical and mental health 2.3 The Ill-Being and Ill-Becoming of child poverty: social inclusion and education 2.4 The subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 149 publications
(57 reference statements)
0
24
0
2
Order By: Relevance
“…In section 3.2 we showed that the principle of equal concern becomes the sole guiding principle for luck egalitarianism in cases regarding inequalities among 8 In this regard, our account of justice for children has important similarities to the view defended by Schweiger and Graf (2015), although their view is grounded in the capability approach of Nussbaum and Sen rather than a pluralist distribuendum of resources and welfare. Also, on a similar basis to my account, Brighouse and Swift (2014) provide a compelling argument to justify the right of children to have parents.…”
Section: Parental Imprisonment and Justice For Childrenmentioning
confidence: 78%
See 3 more Smart Citations
“…In section 3.2 we showed that the principle of equal concern becomes the sole guiding principle for luck egalitarianism in cases regarding inequalities among 8 In this regard, our account of justice for children has important similarities to the view defended by Schweiger and Graf (2015), although their view is grounded in the capability approach of Nussbaum and Sen rather than a pluralist distribuendum of resources and welfare. Also, on a similar basis to my account, Brighouse and Swift (2014) provide a compelling argument to justify the right of children to have parents.…”
Section: Parental Imprisonment and Justice For Childrenmentioning
confidence: 78%
“…In addition to psychological harm, families of prisoners often suffer from the loss of household income as well as other financial costs and burdens associated with prison visits (Arditti 2012;Arditti, Lambert-Shute, and Joest 2003;Murray 2005). This might lead to or increase child poverty, which is a serious ethical concern in its own right (Schweiger 2019;Schweiger and Graf 2015). Here we should note that it is likely that the psychological wellbeing of children of prisoners might further deteriorate in such economically constrained circumstances as well as by a lack of social and emotional support.…”
Section: Parental Imprisonment and Its Impact On The Children Of Prismentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, we suggest that the definition of child growth should not be restricted to physical growth but should rather be expanded to incorporate parental, societal, and other dimensions. The capability approach has been widely applied in studies of child poverty (Biggeri & Mehrotra, 2011;Schweiger & Graf, 2015;Yousefzadeh Daal Faghati & Gossmann, 2016), well-being (Biggeri, Ballet, & Comim, 2011;Fegter & Richter, 2014), and education (Biggeri & Santi, 2012). In child growth, however, the capability approach has not been applied, and this paper aims to explore how a capability approach to child growth could be developed.…”
Section: Towards a Capability Approach To Child Growthmentioning
confidence: 99%